MODELLING THE ECONOMIC IMPACT OF COVID-19: IMPLICATIONS FOR AFRICAN COUNTRIES - Efayena, Obukohwo Oba; Olele, Enoh H (African Journal of Social and Behavioural Sciences, 2020)
This study seeks to build an economic model for the impact of Covid-19 pandemic on economic indicators with far-reaching implications for African economies, given the huge economic challenges of the pandemic. Adopting a modified Solow-Swan (1956) model, the study built a model which incorporated capital stocks and income indicators, and established that the Covid-19 pandemic has implications for capital stocks through savings and investment, and in the long run impact economic output. Therefore, there is urgent need to build an inclusive and resilient policy framework to combat the ravaging effects of the pandemic towards economic recovery and stabilization.